2018
DOI: 10.3390/molecules23092178
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Promotes Adult Neurogenesis in Hippocampal Dentate Gyrus of Mouse through CXCL1/CXCR2 Signaling

Abstract: Astragaloside IV (ASI) has been reported to promote neural stem cells proliferation in vitro and CXCR2 expression on neutrophils. The present study was aimed to investigate the influence of ASI on adult neurogenesis in hippocampal dentate gyrus (DGs) of mouse and to discuss the possible underlying mechanisms. Total number of proliferative cells (BrdU+), pre-mature neurons (DCX+), early proliferative cells (BrdU+/DCX+), proliferative radial gila-like cells (BrdU+/GFAP+) and newly generated neurons (BrdU+/NeuN+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…The mechanism underlying of neurological outcomes improvement by As IV from stroke may be due to enhanced NSCs' proliferation and neurogenesis through activating multiple signaling pathways as reported in previous studies (Yang et al, 2017;Huang et al, 2018;Chen X. et al, 2019). As IV may facilitate the host brain neurogenesis by stimulating and activating the quiesent stem cells in hippocampus.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The mechanism underlying of neurological outcomes improvement by As IV from stroke may be due to enhanced NSCs' proliferation and neurogenesis through activating multiple signaling pathways as reported in previous studies (Yang et al, 2017;Huang et al, 2018;Chen X. et al, 2019). As IV may facilitate the host brain neurogenesis by stimulating and activating the quiesent stem cells in hippocampus.…”
Section: Discussionmentioning
confidence: 59%
“…It has been shown that As IV can not only enhance adult hippocampal neurogenesis (Huang et al, 2018), but also promote NSC proliferation and neurogenesis in transiently ischemic cerebral brains after stroke (Chen X. et al, 2019). In this study, As IV promoted the expression of the DCX, BrdU, and Sox2 proteins in the subgranular zone (SGZ) after stroke in vivo (Figures 2A-D).…”
Section: As IV Promotes Hippocampal Neurogenesis After Stroke and Actmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, long-term peripheral LPS injections for 28 days in adult mice had a long-term negative impact on AHN [121]. In addition to the effect of microglia and the duration of inflammation, some cytokines or chemokines, such as IL-1α, IL-6, IL-10, CX3CL1, CXCL1, and CXCL12 have important roles in positively regulating neurogenesis [124][125][126][127][128][129][130]. The proinflammatory cytokines released by activated microglia or astrocytes, such as IL-1β, TNF-α, IL-18, and IFN-γ, and some chemokines, such as CCL11, negatively impact the proliferation or differentiation of NSCs [131][132][133][134].…”
Section: Known Modulators Of Adult Neurogenesis and The Effects Of Admentioning
confidence: 99%
“…However, there is as yet no direct evidence regarding the impact of exercise on neuroinflammation and neurogenesis in AD animal models. Parachikova et al [217] reported that voluntary exercise in Tg2576 aged mice not only improved their spatial learning ability but also increased hippocampal expression of CXCL1 and CXCL12, which have been reported to have proneurogenic effects [129,130]. Nichol et al [218,219] also reported that exercise reduced the expression of TNF-α and IL-1β in the hippocampus of aged Tg2576 mice.…”
Section: Potential Therapeutic Approaches Targeting Adult Neurogenesimentioning
confidence: 99%